Predictive value of systemic immune inflammation index combined with coagulation index in traumatic coagulopathy in patients with severe trauma: Predicting Traumatic Coagulopathy with Combined Indices - Wang, Chen; Huang, Yongyong; Liao, Shiyun; Song, Jiming (Journal of Medical Biochemistry, 2024)
SummaryBackground: To explore the predictive value of systemic immune inflammation index combined with coagulation index in traumatic coagulation disease (TIC) in patients with severe trauma. Methods: The clinical data of patients with severe trauma treated in our hospital from January 2022 to December 2022 were retrospectively selected. According to the outcome of TIC, the patients were divided into TIC group and non-TIC group, TIC group (n = 50) and non-TIC group (n = 50). The general data, SII and individual indexes of the two groups were compared, and the influencing factors of TIC were analyzed by multivariate Logistics regression. ROC analysis of systemic immune inflammation index combined with blood coagulation index to predict traumatic coagulation in patients with severe trauma.Results: There was no significant difference in general data between the two groups. SII in TIC group was significantly higher than that in non-TIC group. NEU, PLT count, APTT, FIB D and PT in TIC group were higher than those in non-TIC group, while LYM, FIB was lower than that in non-TIC group. Logistics regression analysis showed that APTT, D-Dimer, FIB, PT and SII were independent influencing factors of TIC in patients with severe trauma. The area under the curve of TIC in patients with severe trauma with SII combined with coagulation index was 0.883, and the standard error was 0.032 (95%CI:0.8195~0.9461). The best cut-off value was 0.65.The sensitivity and specificity were 80.3, 84.2 respectively.Conclusions: SII combined with coagulation index has high predictive value for TIC in patients with severe trauma. By monitoring these indexes, we can more accurately predict the occurrence of TIC and take effective treatment measures in time.
Keywords: Systemic immune inflammatory index; coagulation index; severe trauma; traumatic coagulopathy